The Community responsibilities of institutions of higher learning. Comp. and ed. by N. Burns and C.O. Houle. [With contribs of R. Wendell Harrison, G.T. Buswell, I.L. Willis, a.o.] (The University of Chicago Press, 1948)
Proceedings of the Institute for Administrative Officers of Higher Institutions, 1948, vol. 20.